Impact of tourists' psychological ownership of an eco-friendly trail on their behavior intention: an empirical investigation of Jeju Olle Trail in South Korea. Issue 10 (3rd October 2021) - Kim, Jihee; Shin, Hyejo Hailey; Jeong, Miyoung; Lee, Won Seok
ABSTRACT: By adopting psychological ownership theory, this study examines the factors influencing trail visitors' psychological ownership and behavioral intentions. A field survey was conducted with Korean tourists of Jeju Olle Trail, to test determining factors for psychological ownership and the role of commitment in the relationship between psychological ownership and intention to recommend. The results show that tourists' participation and their sense of belonging were key predictors for psychological ownership. In addition, tourists' psychological ownership had a positive influence on their commitment and intention to recommend. This study also discusses theoretical and practical implications along with suggestions for future research.